Reverse engineering in software requirements in web applications using a LEL - Granizo Rodríguez, Angela Verónica (2022)
This document explores and describes the state of the art of Reverse Engineering in the specification of Software Requirements for web applications using an LEL (Language Extended Lexicon). A review of the scientific literature on this topic was carried out with the aim of investigating how the application of Reverse Engineering in the specification of software requirements would improve their quality, with the support of the creation of a tool for web augmentation, that is, a web extension that allows creating a glossary of terms or LEL of web applications, this with the purpose of knowing their operation for maintenance and improvement purposes.